2014
DOI: 10.1038/mp.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Src kinase as a mediator of convergent molecular abnormalities leading to NMDAR hypoactivity in schizophrenia

Abstract: Numerous investigations support decreased glutamatergic signaling as a pathogenic mechanism of schizophrenia: yet molecular underpinnings for such dysregulation are largely unknown. In the postmortem dorsolateral prefrontal cortex, we found striking decreases in tyrosine phosphorylation of N-methyl-D aspartate (NMDA) receptor subunit 2 (GluN2), which is critical for neuroplasticity. The decreased GluN2 activity in schizophrenia may not be due to downregulation of NMDA receptors since MK-801 binding and NMDA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 63 publications
(92 reference statements)
1
50
0
Order By: Relevance
“…Protein folding, trafficking, localization, and recycling are all affected by glycosylation (Dennis et al, 2009; Helenius & Aebi, 2004; Ohtsubo & Marth, 2006; Parodi, 2000), and alterations of these processes in schizophrenia may be linked to abnormalities of glycosylation pathways. Multiple studies have found abnormal subcellular distribution of neurotransmitter receptors and transporters as well as other synaptic proteins in the brain in schizophrenia (Thompson et al, 1998; Talbot et al, 2011; Deo et al, 2012; Hammond et al, 2010; Kristiansen et al, 2010; Shan et al, 2014; Banerjee et al, 2014; Mueller et al, 2015). Interestingly, several studies have shown that neurotransmitter receptors containing abnormally N-glycosylated subunits exhibit abnormal subcellular distribution in schizophrenia brain.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Protein folding, trafficking, localization, and recycling are all affected by glycosylation (Dennis et al, 2009; Helenius & Aebi, 2004; Ohtsubo & Marth, 2006; Parodi, 2000), and alterations of these processes in schizophrenia may be linked to abnormalities of glycosylation pathways. Multiple studies have found abnormal subcellular distribution of neurotransmitter receptors and transporters as well as other synaptic proteins in the brain in schizophrenia (Thompson et al, 1998; Talbot et al, 2011; Deo et al, 2012; Hammond et al, 2010; Kristiansen et al, 2010; Shan et al, 2014; Banerjee et al, 2014; Mueller et al, 2015). Interestingly, several studies have shown that neurotransmitter receptors containing abnormally N-glycosylated subunits exhibit abnormal subcellular distribution in schizophrenia brain.…”
Section: 0 Discussionmentioning
confidence: 99%
“…50 mg amygdala (5 animals were pooled into three samples of 50 mgs in each group, transgenic or wild types) were fractionated into various subcellular fractions using methods previously described (41,42). Protein extracts including PSD fractions were size fractionated in 7.5% Tris Glycine (Biorad, Hercules, CA) gels and western blotted with the following antibodies: PCDH10 (rat OL-protocadherin, clone 5G10, cat# MABT20, Millipore, Billerica, MA); β-actin (mouse, cat# A2228, Sigma, St. Louis, MO); PSD-95 (mouse, cat# 75-028, NeuroMab, Davis, CA); and GLUN1 (goat, cat# sc-1467) GLUN2A (goat, cat# sc-1468), and SRC (mouse, cat# sc-5266), all from Santa Cruz Biotechnology, Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Sample sizes for experiments were chosen based on adequately powered sample sizes used for the same types of data published by our research group and others (22,39,4246). No animals were excluded from the analysis of behavior, VSDi, spine analysis, and biochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…This same meta-analysis found no consistent statistically significant changes in cortical mRNA and protein expression of GluN2 (A, B, D) or GluN3A subunits in schizophrenia, with the exception of reduced GluN2C mRNA in the PFC (Catts et al, 2015; Weickert et al, 2013). In the postsynaptic density fraction obtained from human post-mortem dorsolateral PFC tissue, there is a marked reduction in the activity of signaling cascades downstream of the NMDAR in schizophrenia, despite an apparent increase in NMDAR density and GluN1 expression (Banerjee et al, 2015). In the hippocampus, there have been several reports of reduced GluN1 levels selectively in the dentate gyrus of patients with schizophrenia (X.…”
Section: Nmda Receptor Hypofunction and Schizophreniamentioning
confidence: 99%